Diagnosis and treatment of anemia in patients with inflammatory bowel disease - Mücke, Victoria (Ann Gastroenterol, 2017)
Anemia represents one of the most frequent complications in inflammatory bowel disease (IBD) and severely impairs the quality of life of affected patients. The etiology of anemia in IBD patients can be multifactorial, often involving a combination of iron deficiency (ID) and anemia of chronic disease (ACD). Although current guidelines recommend screening for and treatment of anemia in IBD patients, current observational data suggest that it still remains underdiagnosed and undertreated. Besides basic laboratory parameters (e.g. mean corpuscular volume, reticulocyte count, serum ferritin, transferrin saturation, etc.), the concentration of soluble transferrin receptor (sTfR) and novel parameters such as the sTfR/log ferritin index can guide the challenging task of differentiating between ID and ACD. Once identified, causes of anemia should be treated accordingly. This review summarizes our current understanding of anemia in IBD patients, including the underlying pathology, diagnostic approaches and appropriate anemia treatment regimens.